Hapten synthesis, monoclonal antibody production and immunoassay development for direct detection of 4-hydroxybenzehydrazide in chicken, the metabolite of nifuroxazide. (1st September 2021) - Mari, Ghulam Mujtaba; Li, Hongfang; Dong, Baolei; Yang, Huijuan; Talpur, Aisha; Mi, Jiafei; Guo, Liuchuan; Yu, Xuezhi; Ke, Yuebin; Han, Diangang; Wang, Zhanhui
Highlights: New haptens of nifuroxazide metabolite were firstly designed and synthesized. Effect of hapten structure on affinity and specificity of mAb was studied. High affinity monoclonal antibody to nifuroxazide metabolite was produced. An ELISA was developed for nifuroxazide metabolite without derivatization. Abstract: Derivatization is usually employed in immunoassay for detection of metabolites of nitrofurans and avoiding derivatization could be preferable to achieve an efficient screening. In the study, we designed four haptens of 4-hydroxybenhydrazide (HBH), the nifuroxazide metabolite. The effect of hapten structures on antibody affinity were evaluated and one monoclonal antibody was produced by using the Hapten C with a linear alkalane spacer arm. After optimization, an enzyme linked-immunosorbent assay (ELISA) was established with an 50% inhibition concentration of 0.25 ng mL −1 for HBH, which could ensure the direct detection of HBH without derivatization. The limit of detection of the ELISA for HBH was 0.12 µg kg −1 with the recoveries of 90.1–96.2% and coefficient of variation (CV) values lower than 9.1%. In conclusion, we produced several high affinity antibodies to HBH with new designed hapten and developed an icELISA for the direct detection of HBH without derivatization in chicken.